Innovative capability and financing constraints for innovation: More money, more innovation? - Hanna Hottenrott; Bettina Peters (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2012)
This study presents a novel empirical approach to identify financing constraints for innovation based on the concept of an ideal test (Hall 2008). Firms were offered a hypothetical payment and were asked to choose between alternatives of use. If they selected additional innovation projects, they must have had some unexploited investment opportunities that were not profitable using more costly external finance. We attribute constraints for innovation not only to lacking financing, but also to firms' innovative capability. Econometric results show that financial constraints do not depend on the availability of internal funds per se, but that they are driven by innovative capability.
Keywords: O31; O32; C35; 330; innovation; financing constraints; innovative capability; multivariate probit models; Forschungsfinanzierung; Risikokapital; Verschuldungsrestriktion; Innovation; Probit-Modell; Schätzung; Deutschland